Problematika Pelaksanaan Kurikulum 2013 Pada Pendidikan Anak Usia Dini Di Indonesia - Diana Anggraini (Al-Khair Journal: Management Education, 2021)
Abstract : The Problems of Implementing Curriculum 2013 In Early Childhood Education, the curriculum is seen as the heart of an educational program. Curriculum is a method or strategy designed to achieve educational goals set nationally. All early childhood education and management must understand the framework and structure of the 2013 curriculum for early childhood education to suit the early childhood program, in learning there are still many teachers who lack understanding of the learning curriculum and learning practicesKeywords: Curriculum Development Problems, 2013 Curriculum, Early Childhood Education in Indonesia Abstrak : Problematika Penerapan Kurikulum 2013 Pada Pendidikan Anak Usia Dini,kurikulum dipandang sebagai jantunnya sebuah program pendidikan.kurikulum merupakan suatu cara atau strategi yang dirancang untuk mencapai tujuan pendidikan yang ditetapkan secara nasional. Seluruh pendidikan dan pengelolaan PAUD harus memahami kerangka dan struktur kurikulum 2013 pendidikan anak usia dini agar sesuai dengan program paud, dalam pembelajaran masih banyak guru yang kurang pemahamannya dalam kurikulum pembelajaran dan praktek pembelajaranKata kunci : Problematika Perkembangan Kurikulum, Kurikulum 2013, Pendididkan Anak Usia Dini di Indonesia.